A Study about The Quality of Nursing Services a Hospitals' Ward, Mojokerto - Abdul Muhith; Nurwidji Nurwidji (Universitas Airlangga, 2016)
Introduction: Nowadays, the trend of hospital visits in Mojokerto is declining. It can caused by man (nurses), such as the quality of nursing services hasn't been conducted optimally. This study was aimed to analyze the quality of nursing services at hospitals' ward at Mojokerto. Method: This was explanatory research with survey method and cross sectional approach. The population were nurses and patients who undergo hospitalization minimally in three days at RSU. Dr. Wahidin Sudiro Husodo and RS Reksa Waluyo Mojokerto. The data were collected by using questionnaire, and then will be analyzed by using regression statistical test. Result: 1) There was positive significance influence of nurses capability, hospital's ethic, and leadership to the commitment of nurses; 2) There was significant influence of capability work (identification, significance, autonomy, and feedback) to the improvement of nursing services quality; 3) There was significant influence of hospital's ethics (communication, relatedness with industry, compulsion, and specification) to the improvement of nursing services quality; 4) There was significant influence of leadership (challenger risk, socialization in vision and mission, supporter, guiding, and supporting) to the improvement of nursing services quality; 5) There was significant influence of nurses' commitment (sense of belonging, sense of linking, believable leader, and suitability of value) to the improvement of nursing services quality. Discussion: It can be concluded that in order to improve the quality of nursing service, management of RSU Dr. Wahidin Sudiro Husodo and RS Rekso Waluyo Mojokerto should improve the ability of nurses, the enforcement of hospital ethics to all employees without exception, and develop hospital ethics that can represent various stakeholder interests, as well as maintain and improve leadership issue. Keywords: nurses, quality, services (tangibility, reliability, responsiveness, assurance, empathy)